Pelaksanaan Program Pengembangan Profesionalitas Guru Di SMA Negeri 3 Bengkulu Selatan - Marlita, Septi; Danim, Sudarwan; Sumarsih (UNIVERSITAS BENGKULU, 2024)
, the purpose of this study is to describe; the process of the teacher professional development program which includes; program planning, program implementation, follow-up and obstacles to the professional development program for teachers at State Senior High School 3 Bengkulu Selatan. This analysis technique basically consists of three components, namely data reduction, data presentation, and description and sentence verification. The results of this study are; (1) The planning of the teacher professional development program exists but has not been fully implemented, (2) The implementation of the teacher professional development program has not yet been implemented in accordance with the existing program. (3) There is a follow-up to the teacher professional development program at South Bengkulu State Senior High School 3, but it does not have a positive impact on the implementation of the teacher professional development program. (4) The factors inhibiting the teacher professional development program are; (a) external factors, and (b) internal factors. As a follow-up to the research on the implementation of the teacher professional development program at South Bengkulu 3 Senior High School, namely; There needs to be a revision of the formulation and scheduling of teacher professional development programs to run in accordance with the targets to be achieved